Implementación y configuración de una red lan con tecnología ipv4 bajo la plataforma windows para proveer servicios en el laboratorio de redes y mantenimiento en la Universidad Técnica de Cotopaxi extensión La Maná - Chito Toapanta, Rosa Herminia (2015)
Nowadays, the Lan configuration has become a technological element which does not require more investment than the material and knowledge, also; there are several technologies that help professionals to define optimal performance….